Ethylene signaling in rice and Arabidopsis: New regulators and mechanisms - Zhao, He; Yin, Cui‐Cui; Ma, Biao; Chen, Shou‐Yi; Zhang, Jin‐Song (Journal of integrative plant biology, 2021)
Ethylene is a gaseous hormone which plays important roles in both plant growth and development and stress responses. Based on studies in the dicot model plant species Arabidopsis, a linear ethylene signaling pathway has been established, according to which ethylene is perceived by ethylene receptors and transduced through CONSTITUTIVE TRIPLE RESPONSE 1 (CTR1) and ETHYLENE‐INSENSITIVE 2 (EIN2) to activate transcriptional reprogramming. In addition to this canonical signaling pathway, an alternative ethylene receptor‐mediated phosphor‐relay pathway has also been proposed to participate in ethylene signaling. In contrast to Arabidopsis, rice, a monocot, grows in semiaquatic environments and has a distinct plant structure. Several novel regulators and/or mechanisms of the rice ethylene signaling pathway have recently been identified, indicating that the ethylene signaling pathway in rice has its own unique features. In this review, we summarize the latest progress and compare the conserved and divergent aspects of the ethylene signaling pathway between Arabidopsis and rice. The crosstalk between ethylene and other plant hormones is also reviewed. Finally, we discuss how ethylene regulates plant growth, stress responses and agronomic traits. These analyses should help expand our knowledge of the ethylene signaling mechanism and could further be applied for agricultural purposes. Ethylene plays vital roles in plant growth and development and stress responses. In this review, we summarize the latest progress and compare the conserved and divergent aspects of the ethylene signaling pathway between Arabidopsis and rice. The agricultural significance of ethylene signaling in crops is also discussed.